ERA5 Reanalysis Monthly Means ... - European Centre For Medium-Range Weather Forecasts (UCAR/NCAR - Research Data Archive, 2017)
Please note: Please use ds633.1 to access RDA maintained ERA-5 Monthly Mean data, see ERA5 Reanalysis (Monthly Mean 0.25 Degree Latitude-Longitude Grid), RDA dataset ds633.1. This dataset is no longer being updated, and web access has been removed.After many years of research and technical preparation, the production of a new ECMWF climate reanalysis to replace ERA-Interim is in progress. ERA5 is the fifth generation of ECMWF atmospheric reanalyses of the global climate, which started with the FGGE reanalyses produced in the 1980s, followed by ERA-15, ERA-40 and most recently ERA-Interim. ERA5 will cover the period January 1950 to near real time, though the first segment of data to be released will span the period 2010-2016.ERA5 is produced using high-resolution forecasts (HRES) at 31 kilometer resolution (one fourth the spatial resolution of the operational model) and a 62 kilometer resolution ten member 4D-Var ensemble of data assimilation (EDA) in CY41r2 of ECMWF's Integrated Forecast System (IFS) with ...